Prescribing for children at the interfaces of care. Issue 4 (5th August 2012) - Terry, David; Sinclair, Anthony
Abstract : Prescribing for children at the primary–secondary/tertiary care interface is more complex than that for adults. Children often need unlicensed medicines and there may be issues over who will prescribe such items. There may also be issues in obtaining unlicensed medicines (specials) from community pharmacists. This article reviews the current arrangements in England relating to prescribing for children at the interfaces of care and describes the following: prescribing responsibility, shared-care arrangements, medication continuity on admission and discharge from hospital, unlicensed medicines, continuing-care medication arrangements and highlights potential service changes to maintain access to medicines for children.